(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2024)
A research article is a type of academic writing that presents original research and analysis on a specific topic. Unlike other types of academic writing, such as essays or book reviews, research articles are based on primary sources, such as date collected through experiments or surveys. Research articles typically follow a specific a structure, including an abstract, introduction, methods, results, and conclusion. This structure helps to ensure that the research is presented in a clear and organized manner, marking it easier for readers to understand and evaluate the findings.